Analysis Of The Needs Of Academic Information Systems At Pondok Modern Darussalam Gontor - Fathur Rozi, Moh. 'Ainun Najmiz Zuhry (2025)
This research departs from the main problem in many Islamic Boarding Schools, where the management of academic data, such as student data, grades, and administration, is still carried out manually. In today's digital era, the use of Management Information Systems (SIM) is very important to improve the efficiency and effectiveness of data management. Therefore, the main purpose of this study is to analyze the need for the implementation of the Academic Information System (SIA) at Pondok Modern Darussalam Gontor and evaluate its impact on the management of academic and non-academic data. The method used is a qualitative approach with case studies. Data was collected through in-depth interviews with teachers, administrative staff, and parents of students, as well as direct observation and document analysis. The results of the study show that the use of driver's license has had a significant positive impact. The use of driver's licenses can improve data accuracy, speed up the administrative process, and facilitate access to information for all interested parties. Overall, this study concludes that SIM makes an important contribution to data management in Islamic Boarding Schools. Despite the challenges in implementation, such as resistance to technology and the need for training, strong support from school leaders proved to be a key factor in the successful use of driver's licenses. Keywords: Academic Information System, Islamic Boarding School, Needs Analysis, Educational Technology, Data Management.